Pengembangan PAUD Berbasis Keluarga untuk Meningkatkan Ketrampilan Pengasuhan - Jazariyah Jazariyah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
Alignment between early childhood education (PAUD) in the family with the implementation of education in early childhood institutions become a key to optimal development of early childhood. Parents with good parenting skills can be a factor supporting the PAUD institution in achieving its vision and mission. Family-Based Early Childhood where there are some activities involving parents can be a bridge to establish cooperation between parents, educators and institutional managers. For this purpose, this research is conducted in an effort to develop family-based PAUD program, by creating a practical module that can be used by educators and parents. Research results show that the developed product is feasible to be used as an independent learning media that can be used by parents. This is based on the average score of the overall validator in this case media experts, material experts, peers and educators obtained score of 4.53 which is in the category of "very good". Furthermore, based on the pretest results with the value of 23.3 and posttest a number of 32.27 indicates an increase in knowledge of upbringing of 8.9 with a standard gain of 0.75 in the "high" category. Observation of parenting activities shows an average score of 4.6 in 92% percentage that is categorized as "very high". Based on these results, the modules developed are effective in improving parenting skills.